(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2010)
The phenomenon of pedagogical trade of a teacher at higher school. In the article the essence is analyzed of the phenomenon of pedagogical trade of psychology teacher at higher school, his displays are found out in relation to personality and activity levels.